Fetomaternal outcome in pregnancies with abnormal liquor volume - a prospective observational study - Punithavathi J; Pillai Arthi Karunanithi; Nuzhat Zeba (Barpeta Obstetrics and Gynaecological Society, 2022)
Objective: The present study was conducted to study fetomaternal outcomes in oligohydramnios and polyhydramnios. Methods: This prospective observational study was conducted in the department of obstetrics and gynecology at Dhanalakshmi Srinivasan Medical College and Hospital, Perambalur, on 150 cases of oligohydramnios and 50 cases of polyhydramnios. Amniotic fluid index was calculated according to Phelan index. Women with amniotic fluid index (AFI) of ≥ 25 were taken as polyhydramnios group, and AFI of ≤ 5 were taken as oligohydramnios group. These women were closely monitored throughout their antenatal, intrapartum, and postpartum period until one week after birth. Categorical outcomes were compared between study groups using the chi-square test. P value < 0.05 was considered statistically significant. Result: In the present study, majority of the oligohydramnios patients underwent cesarean section (CS) (61.33%) and fetal distress (78.26%) was the common cause for CS. Preeclampsia (66.67%) was found to be the major maternal complication in the oligohydramnios group and GDM (53.33%) in the polyhydramnios patients. Majority of the babies of oligohydramnios patients had low birth weight (56.94%). A high perinatal mortality rate was observed in the polyhydramnios (28%) group and more than half of the babies (53.33%) of the oligohydramnios patients were admitted in NICU compared to 28% in the polyhydramnios group. Conclusion: The abnormal liquor volume is often associated with an increased incidence of labor complications, cesarean section, and adverse perinatal outcomes.